Practical possibilities of inflammatory markers use in the evaluation of ischemic heart disease - Nowicka, Grażyna (Przewodnik Lekarza/Guide for GPs, 2005)
Since the role of inflammatory process in the pathogenesis of atherosclerosis acute coronary events has been documented, one focused on inflammatory markers as useful parameters in the diagnosis of these clinical situations. The research evidently indicate that C-reactive protein (CRP) is one of the most useful inflammatory markers in the clinical practice. It is useful in the risk evaluation of myocardial infection incidence in subjects with documented ischemic heart disease as well as in asymptomatic patients. The CRP concentration is the independent risk indicator from other factors universally used in clinical practice for assessment of ischemic heart disease risk. CRP is the only inflammatory marker recommended nowadays to be used in clinical practice for assessment of prognosis in the primary as well as secondary prevention.